ANALISA POTENSI PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) di DISTRIK ABENAHO KABUPATEN YALIMO - Otius Kogoya (Jurnal Teknik Sipil Info Manpro, 2024)
This study examines the feasibility of the location for the construction of a micro hydro power plant (PLTMH) in Landikma Village, Abenaho District, in relation to the district government's plans. The specific objectives of this study are to determine the potential location of a PLTMH based on the applicable technical principles, as well as to compile a feasibility study for the construction of a PLTMH to support lighting/electricity services. The survey method was applied to identify the description of the existing conditions, with reference to the criteria for PLTMH development. Data analysis was carried out using quantitative and qualitative methods. Based on the research results, the PLTMH construction site in Landikma Village, Abenaho District, Yalimo Regency meets the eligibility to build a 177kW micro-hydro power plant. The river discharge at the location of the development plan is 0.950 m3/s, so the result of calculating the potential electric power generated by the PLTMH is 326.2 kW. This electrical energy is capable of meeting the lighting needs of 521 houses, assuming that each house gets 450 watts of electric power. Strategic environmental studies need to be carried out to ensure that this development does not have the potential to cause negative impacts on the environment. The PLTMH development process must also be accompanied by a comprehensive Detail Engineering Design (DED). In addition, local communities must also be involved in the process of reviewing the development, evaluation and supervision to ensure the sustainability of development and the sustainability of natural resources around the PLTMH construction site. Keywords: Potential Study, power plant, micro hydro, turbine, river.